The Influence Of Awareness And Service Quality On Taxpayer Compliance In Paying Land And Building Tax In Bunga Mas Village South Of Bengkulu Regency - Wahyu, Lakon; Yulianti , Oni; Fitriano , Yun (Utami Publisher, 2025)
Tax is one of the most important sources of state revenue besides other revenues, such as oil and gas revenues and non-tax revenues. The government is continuously trying to increase the target of state revenue from the tax sector. This research is explanatory research. The objectives to be achieved in this study are: To find out whether awareness affects taxpayer compliance in paying Land and Building Tax (PBB) in Bunga Mas Village, South Bengkulu Regency. To find out whether service quality affects taxpayer compliance in paying Land and Building Tax (PBB) in Bunga Mas Village, South Bengkulu Regency. The results of this study are The effect of awareness (X1) on taxpayer compliance (Y) based on the results of the t-test for the awareness variable (X1) is 2.589, the t-value is compared to the t-table of 1.665. because tcount>ttable (2.589>1.665) with a significant level of 0.003<5% then Ha is rejected and Ho is accepted The effect of service quality (X2) on taxpayer compliance (Y) based on the results of the tcount test for the service quality variable (X2) is 3.763 the tcount value when compared with the ttable is 1.665 because tcount>ttable (3.763>1.665) with a significant level of 0.002<5% then Ha is accepted and Ho is rejected The Ftable result is 2.95 because Fcount>Ftable (7.894>2.95) then Ha is accepted and Ho is rejected meaning that there is a significant effect of the awareness variable (X1) and service quality (X2) together or simultaneously on taxpayer compliance (Y) The coefficient value of the Adjusted R Square R2 = 0.780. This value means that the independent variables together contribute 78% in influencing the dependent variable with moderate criteria.